2005
DOI: 10.1111/j.1471-0528.2004.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic sterilisation: a study of women's attitudes to a novel procedure

Abstract: Laparoscopy is the most common mode of surgery for female tubal sterilisation. Hysteroscopic sterilisation is a new method which can be performed in the outpatient setting under local anaesthetic. We carried out a prospective cohort trial to determine whether women would actually favour hysteroscopic sterilisation over laparoscopic sterilisation. Data analysis in a cohort of 96 women showed that 77% would prefer laparoscopic sterilisation over the hysteroscopic procedure (23%), despite the advantages of an out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
(8 reference statements)
0
12
0
1
Order By: Relevance
“…Les temps d'hystéroscopie sont très variables et sont actuellement plus courts que ceux de notre série [12][13][14][15][16].…”
Section: Discussionunclassified
“…Les temps d'hystéroscopie sont très variables et sont actuellement plus courts que ceux de notre série [12][13][14][15][16].…”
Section: Discussionunclassified
“…This in turn could lead to difficulties in patient recruitment. This turned out to be the case during the pilot study with less than 8% of women approached willing to be randomised 7 . The majority of women expressed a preference for laparoscopic sterilisation, the most common reason being a desire to ‘be asleep’.…”
Section: Methodsmentioning
confidence: 98%
“…This turned out to be the case during the pilot study with less than 8% of women approached willing to be randomised. 7 The majority of women expressed a preference for laparoscopic sterilisation, the most common reason being a desire to 'be asleep'. The main reason women preferred hysteroscopic sterilisation was the 'quick recovery period'.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 72% classed HSG as acceptable. Data analysis in a cohort of 96 women in the UK 25 showed that 77% would prefer laparoscopic sterilisation over the hysteroscopic procedure (23%), despite the advantages of an outpatient setting. Age, obstetric history, employment and marital status, access to transport and previous anaesthetic did not significantly influence the choice made.…”
Section: Women's Perspectivementioning
confidence: 99%